The Protection of Health in the Care and Trust Relationship between Doctor and Patient: Competence, Professional Autonomy and Responsibility of the Doctor and Decision-Making Autonomy of the Patient - Delbon, Paola (Journal of public health research, 2018)
The Authors review Law No. 219/2017, with its important contribution to defining the roles and responsibilities of subjects in care relationship – a dynamic relationship (over time, for the condition of the interested party, to people who may be involved) – and regulating advance directives and shared planning of care. The Law promotes and enhances the relationship of care and trust between doctor and patient, which includes the competence, professional autonomy and responsibility of the doctor and the decisional autonomy and right to self-determination – to make an informed and voluntary choice about treatment proposed by the doctor - of the patient. For concrete implementation of the Law, an adequate information system and all the measures to guarantee certainty about the consequences of behaviour and protection of the rights of all the subjects involved are now essential. In addition, for advance directives, it is essential to reflect on the adequacy of medical information required by the Law itself for its drafting, considering that the citizen can contact qualified professionals and also independently find this information autonomously, selecting the sources of information.